A 2000 year-long proxy and observational reconstruction of Central Asian climate. (1st November 2019) - Rodda, Charles; Birkel, Sean; Mayewski, Paul
Abstract: Central Asia (CA) is one of the most arid places on Earth and climate change threatens to disrupt the natural hydrologic systems that store its limited annual wet-season precipitation in glaciers and release it during the dry season. Warm/Wet and Cold/Dry periods recorded over the last 2000 years using multiple paleoclimate proxy records reflect a local hydrocycle dominated by the Westerlies and moisture recycling within the Aral Sea catchment. The best tool for assessing recent climate trends is modern reanalysis modeling, ground-truthed by weather station data. Using the best-fit reanalysis, we find warming and drying trends have dominated the region over the last 115 years. Continued warming and drying in glacierized eastern CA during the critical spring season when glaciers typically increase in mass increase the likelihood that human infrastructure will be needed to impound wet-season precipitation. Highlights: Paleorecords define the range of moisture delivery to Central Asia since 2, 000yBP. The ERA-Interim reanalysis model is the best-fit model in Central Asia. Moisture in Central Asia collects in glaciers during a critical wet/cold spring season, but that relationship is threatened. Modern moisture trends should be considered for water resource planning in CA.